The Bank of England as Lender of Last Resort: New historical evidence from daily transactional data - Mike Anson; David Bholat; Miao Kang; Ryland Thomas (European Historical Economics Society (EHES), 2017)
We use daily transactional ledger data from the Bank of England's Archive to test whether and to what extent the Bank of England during the mid-nineteenth century adhered to Walter Bagehot's rule that a central bank in a financial crisis should lend cash freely at a high interest rate in exchange for 'good' securities. The archival data we use provides granular, loan-level insight on the price and quantity of credit, and information on its distribution to particular counterparties. We find that the Bank's behaviour during this period broadly conforms to Bagehot's rule, though with variation across the crises of 1847, 1857 and 1866. Using a new, higher frequency series on the Bank's balance sheet, we find that the Bank did lend freely, with the number of discounts and advances increasing during crises. These loans were typically granted at a rate above pre-crisis levels and, in 1857 and 1866, typically at a spread above Bank Rate, though we also find some instances in the daily discount ledgers where individual loans were made below Bank rate in 1847. Another set of customer ledgers shows that the securities the Bank purchased were debts owed by a geographically and industrially diverse set of debtors. And using new data on the Bank's income and dividends, we find the Bank and its shareholders profited from lender of last resort operations. We conclude our paper by relating our findings to contemporary debates including those regarding the provision of emergency liquidity to shadow banks.
Keywords: E58; G01; G18; G20; H12; N2; N4; N8; 330; Bank of England; lender of last resort; financial crises; financial history; central banking